Earthquakes, Fuel Crisis, Power Outages, and Health Care in Nepal: Implications for the Future. (18th April 2017) - Adhikari, Bipin; Mishra, Shiva Raj; Babu Marahatta, Sujan; Kaehler, Nils; Paudel, Kumar; Adhikari, Janak; Raut, Shristi
Abstract: Earthquakes are a major natural calamity with pervasive effects on human life and nature. Similar effects are mimicked by man-made disasters such as fuel crises and power outages in developing countries. Natural and man-made disasters can cause intangible human suffering and often leave scars of lifelong psychosocial damage. Lessons from these disasters are frequently not implemented. The main objective of this study was to review the effects of the 2015 earthquakes, fuel crisis, and power outages on the health services of Nepal and formulate recommendations for the future. The impacts of earthquakes on health can be divided into immediate, intermediate, and long-term effects. Power outages and fuel crises have health hazards at all stages. It is imperative to understand the temporal effects of earthquakes, because the major needs soon after the earthquake (emergency care) are vastly different from long-term needs such as rehabilitation and psychosocial support. In Nepal, the inadequate and nearly nonexistent specialized health care at the peripheral level claimed many lives during the earthquakes and left many people disproportionately injured. Preemptive strategies such as mobile critical care units at primary health centers, intensive care training for health workers, and alternative plans for emergency care must be prioritized. Similarly, infrastructural damage led to poor sanitation, and alternative plans for temporary settlements (water supply, food, settlements logistics, space for temporary settlements) must be in place where the danger of disease outbreak is imminent. While much of these strategies are implementable and are often set as priorities, long-term effects of earthquakes such as physical and psychosocial supports are often overlooked. The burden of psychosocial stresses, including depression and physical disabilities, needs to be prioritized by facilitating human resources for mental health care and rehabilitation. In addition, inclusion of mental health and rehabilitation facilities in government health care services of Nepal needs to be prioritized. Similarly, power outages and fuel crises affect health care disproportionately. In the current context where permanent solutions may not be possible, mitigating health hazards, especially cold chain maintenance for essential medicines and continuation of life-saving procedures, are mandatory and policies to regulate all health care services must be undertaken. ( Disaster Med Public Health Preparedness . 2017;11:625–632)